Prioritizing Human Resource Competency Development and Financial Management in MSMEs Using the Analytic Hierarchy Process (AHP) - Ayu Gede Willdahlia; Ni Made Sudianti; Eko Maisusanto; Ni Made Astini Rahayu (Jurnal Krisnadana, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in supporting economic growth and employment, particularly in developing countries such as Indonesia. Despite their significant contribution to the national economy, many MSMEs still face internal challenges related to human resource competencies and financial management. These limitations often hinder business sustainability and competitiveness. Therefore, determining priority development strategies is essential to optimize the limited resources available to MSME actors.This study aims to analyze the priority factors for MSME development through human resource competency and financial management using the Analytic Hierarchy Process (AHP) method. The research was conducted in Denpasar City, Bali, involving 17 respondents consisting of MSME owners, academics, business consultants, and financial practitioners selected through purposive sampling. Data were collected using pairwise comparison questionnaires based on Saaty’s scale and analyzed through AHP procedures, including hierarchy structuring, pairwise comparison matrix construction, normalization, priority weight calculation, and consistency testing.The results show that human resource competency is the most important factor in MSME development compared to financial management. Among the human resource sub-criteria, digital literacy has the highest priority, followed by training, experience, and education. Meanwhile, in financial management, financial recording is identified as the most important sub-criterion, followed by budgeting, cost control, and financial planning. These findings indicate that strengthening digital competencies and improving systematic financial recording practices are key priorities for enhancing MSME performance and sustainability.This research provides practical implications for MSME development programs by emphasizing the importance of targeted training and financial management improvements. The results can serve as a reference for policymakers, practitioners, and MSME actors in designing more effective strategies to support sustainable MSME growth.